Proof-of-principle of onchocerciasis elimination with ivermectin treatment in endemic foci in Africa: final results of a study in Mali and Senegal. - Mamadou O Traore; Moussa D Sarr; Alioune Badji; Yiriba Bissan; Lamine Diawara; Konimba Doumbia; Soula F Goita; Lassana Konate; Kalifa Mounkoro; Amadou F Seck; Laurent Toe; Seyni Toure; et al. (PLoS Neglected Tropical Diseases, 2012)
BACKGROUND: Mass treatment with ivermectin controls onchocerciasis as a public health problem, but it was not known if it could also interrupt transmission and eliminate the parasite in endemic foci in Africa where vectors are highly efficient. A longitudinal study was undertaken in three hyperendemic foci in Mali and Senegal with 15 to 17 years of annual or six-monthly ivermectin treatment in order to assess residual levels of infection and transmission, and test whether treatment could be safely stopped. This article reports the results of the final evaluations up to 5 years after the last treatment. METHODOLOGY/PRINCIPAL FINDINGS: Skin snip surveys were undertaken in 131 villages where 29,753 people were examined and 492,600 blackflies were analyzed for the presence of Onchocerca volvulus larva using a specific DNA probe. There was a declining trend in infection and transmission levels after the last treatment. In two sites the prevalence of microfilaria and vector infectivity rate were zero 3 to 4 years after the last treatment. In the third site, where infection levels were comparatively high before stopping treatment, there was also a consistent decline in infection and transmission to very low levels 3 to 5 years after stopping treatment. All infection and transmission indicators were below postulated thresholds for elimination. CONCLUSION/SIGNIFICANCE: The study has established the proof of principle that onchocerciasis elimination with ivermectin treatment is feasible in at least some endemic foci in Africa. The study results have been instrumental for the current evolution from onchocerciasis control to elimination in Africa.